Memperjuangkan Kepentingan Perempuan: Analisis Praktik Mediasi pada Permohonan Izin Poligami di Pengadilan Agama dalam Perspektif Feminisme Jurisprudence - Khoirul Sodiq; Mahfud; Nuri Safitri (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
In principle, the prescription of polygamy in Islam is intended to protect the interests and rights of women, as can be traced through the historical context of Qur’anic verses and hadith. However, in practice, applications for polygamy permits submitted to the Religious Courts are predominantly driven by reasons that reflect male interests in hegemonizing women within the domestic sphere. Mediation implemented in the Religious Courts in polygamy permit cases serves as a deliberative forum aimed at advocating women’s interests in a more persuasive manner. This article aims to analyze the practice of mediation in polygamy permit applications in the Religious Courts using a gender justice approach. The primary data in this study consist of statutory regulations, including the Supreme Court Regulation on Mediation, the Marriage Law, and the Compilation of Islamic Law. Secondary data include journal articles, conference proceedings, books, undergraduate theses, master’s theses, and dissertations relevant to the research topic. Data were collected through documentation techniques and analyzed using a qualitative-inductive method. Feminist Jurisprudence theory is employed as the analytical framework in this study. The findings indicate that the implementation of mediation in polygamy permit cases in the Religious Courts has not fully reflected a gender justice paradigm, as it is still characterized by unequal power relations between husbands and wives. Mediation procedures tend to be formalistic and do not provide a safe deliberative space for women to freely express their objections. Through the critique of Feminist Jurisprudence theory, this study highlights the need to reformulate mediation regulations to better align with the principles of substantive justice. Such reform includes gender-perspective training for mediators and the strengthening of mediation methods that equally protect the rights and interests of women.